Penerapan Metode Phonetic Placement pada Disartria Unilateral Upper Motor Neuron: Studi Kasus Tunggal - Junaeni; Jumiarti Jumiarti; Fildza Khalisha (Jurnal Terapi Wicara, 2025)
Background: Unilateral Upper Motor Neuron (UUMN) dysarthria is a type of dysarthria characterized by damage to the upper motor neurons, causing articulation disorders as the most dominant symptom. Speech therapy intervention is essential in this condition.Objective: This study aims to determine the effectiveness of the Phonetic Placement method in improving articulation skills in patients with UUMN dysarthria.Methods: This study used a single-subject experimental design with a one-group pretest–posttest approach. The research subject was a 51-year-old woman with a history of UUMN dysarthria. The intervention was conducted over 10 sessions using the Phonetic Placement method, which focused on word-level articulation exercises. Perceptual assessment was conducted to evaluate articulation clarity by comparing abilities before and after therapy.Results: There was no significant change in the ability to produce target phonemes at the word level. Conclusion: The Phonetic Placement method has not shown effectiveness in improving articulation in this case, possibly due to the limited number of therapy sessions. Further research is recommended with more frequent therapy, repetition, and combination with other methods. Keywords: UUMN dysarthria, Articulation, Phonetic Placement.